Water and electrolyte imbalance in patients with metabolic syndrome - V. N. Pavlov; A. V. Alekseyev; R. R. Ishemgulov; A. A. Ismailov; Zh. A. Galeyeva (Бюллетень сибирской медицины, 2012)
Considering the high incidence of renal impairment in metabolic syndrome (MS), an analysis of electrolyte metabolism was performed in 112 patients preoperatively and 53 patients postoperatively. Aldosterone level, adrenocorticotropic hormone level, neutrophil gelatinase-associated lipocalin level, cortisol level, β2-microglobulin level, serum vasopressin level, urinary microalbumin level measurements were taken as a combined patient assessment procedure. MS patients were found to demonstrate a decrease in circadian amounts of urea, potassium, sodium and chlorides excretion. An increase in vasopressin production and an enhancement of microalbumin excretion were detected. The specified disturbances developed as «a vicious circle»: fluid retention resulted in heperfiltration, with renal dysfunction leading to a deteriorated hydro-electrolyte imbalance. An improvement of circadian electrolyte excretion rates, as well as a decline in vasopressin and cortisol levels, occurred due to a reduction of abdominal fat volume.